O-32 The exposure-response relation between occupational exposure to respirable crystalline silica and incident interstitial lung diseases: a prospective follow-up study. (14th March 2023) - Kolstad, Henrik A; Vestergaard, JM; Thorup, KS; Thygesen, J; Rasmussen, F; Andersen, MB; Bendstrup, E; Stokholm, ZA; Ohlander, J; Peters, S; Würtz, ET; Schlünssen, V; et al.
Abstract : Introduction: Occupational exposure to respirable crystalline silica is a well-known cause of silicosis, but studies have indicated that silica exposure is also associated with increased risk of other types of interstitial lung disease (ILD). Our objective was to examine the risk of different types of ILD following occupational silica exposure. Material and Methods: The study population includes the total Danish working population of 5, 478, 664 workers, followed 1979–2015. Annual individual exposure to respirable crystalline silica was estimated using a quantitative job exposure matrix. Cases of ILD were identified in the National Patient Register. We conducted adjusted analyses of exposure-response relations between cumulative silica exposure and different types of ILD. Register studies in Denmark without biological materials do not need approval from the National Committee of Health Research Ethics. This study is approved by the Danish Data Protection Agency. Results: The risk of silicosis increased with increasing cumulative exposure with an incidence rate ratio (IRR) of 3.07 (95% confidence interval (CI) 2.40–3.93) in the highest exposure group (the highest tertile among the silica exposed) compared to the non-exposed group. The risk of other pneumoconioses was also increased with an IRR of 1.18 (95% CI 1.05–1.33) for the highest exposed compared to the non-exposed. For idiopathic ILD, ILD associated with connective tissue disease and other ILD the risks were increased in the highest exposure group compared to the non-exposed, but the analyses did not show clear exposure-response patterns. Conclusion: This study confirms an exposure response relation for occupational silica exposure and silicosis and indicates increased risks for other types of ILD. This warrants further examination of the specific risk patterns for different types of ILD.